Postoperative Ileus: Comparative Pathophysiology and Future Therapies - Hellstrom, Emily A.; Ziegler, Amanda L.; Blikslager, Anthony T. (Frontiers in Veterinary Science, 2021)
Postoperative ileus (POI), a decrease in gastrointestinal motility after surgery, is an important problem facing human and veterinary patients. Retrospective study indicates that 37.5% of horses that develop POI following small intestinal resection will not survive to discharge. The two major components of POI pathophysiology are a neurogenic phase which is then propagated by an inflammatory phase. Perioperative care has also been implicated, namely the use of opioid therapy, inappropriate fluid therapy and electrolyte imbalances. Current therapy for POI variably includes an early return to feeding to induce physiological gastrointestinal motility, reducing the inflammatory response with agents such as non-steroidal anti-inflammatory drugs, and use of prokinetic therapy such as lidocaine. However, optimal management of POI remains controversial. A better understanding of the roles of the gastrointestinal microbiota, intestinal mucosal barrier function, the post-surgical inflammatory response, as well as enteric glial cells, a component of the enteric nervous system, in modulating postoperative motility and the pathogenesis of POI may provide future targets for prevention and/or therapy of POI.